A digital signature scheme based on shared key in intelligent terminal - Guorong LIU; Dongxin LIU; Laifu WANG; Jun SHEN; Huamin JIN (Dianxin kexue)
In traditional internet,digital certificate in USB key is the most mature technology of application security assurance.But it is difficult to use in mobile internet,because of the restriction of intelligent terminal interface.A digital signature scheme based on shared key in intelligent terminal was discussed to lower the threshold.The shared key supported multiple digital certificates,and was shared by multiple applications through the unified management.After that,the security of the scheme was analyzed,and a scheme integrated digital certificate and fingerprint identification was discussed to enhance user convenience.